Uji Bakteri Total Coliform dan Escherichia coli Pada Sumber Mata Air Ubalan Desa Maguan Kecamatan Ngajum Kabupaten Malang - Octavia Shahilla Aniansyah; Ahmad Syauqi; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Water is a very important human need and no life can exist without air. Human needs are generally obtained from various sources, both from groundwater, surface water and rainwater. Ubalan is a hamlet located in Ngajum District, Malang Regency. The location is under the foot of Mount Kawi - Malang which has a natural spring and is generally channeled by the surrounding community to fill artificial ponds and also used by the community to meet their daily needs. The use of spring sources is generally very diverse, including for drinking water, fisheries, conservation and as a tourist attraction. Water indicators such as total coliform bacteria and Escherichia coli. Regarding this statement, it is necessary to carry out a microbiological test to test for total coliform and Escherichia coli bacteria at the Ubalan spring, Maguan Village, Ngajum District, Malang Regency, which is a tourist attraction location that is never empty of visitors. The research method used is survey method and descriptive laboratory analysis. To take samples of air sources carried out randomly. The test results for Total Coliform and Escherichia coli bacteria in West Sumatra Mata Air Ubalan, Maguan Village, Ngajum District, Malang Regency, showed that the MPN results index was at station 3 (0.273) station 2 (0.188) and the lowest was at station 1 (0.138). The analysis is related to the level of the presence of total coliform and E. coli bacteria with pollutant source factors that are thought to come from human activities around the source, community behavior and the distance factor between air sources and exhaust locations. Correlation of research results obtained by the presence of total coliform bacteria and Escherichia coli in the air source with the relationship of factors between the supporting bacteria showed (p value = 0.188) which means it did not have a significant effect.